ARTIFICIAL INTELLIGENCE (AI)-BASED MOBILE LEARNING IN ELT FOR EFL LEARNERS: THE IMPLEMENTATION AND LEARNERS' ATTITUDES - Dilyorjon Solidjonov (University Research Base, 2024)
This article explores the integration of Artificial Intelligence (AI) into mobile learning environments for English Language Teaching (ELT) among English as a Foreign Language (EFL) learners. The theoretical foundations, practical implementations, and empirical findings regarding AI-based mobile learning in ELT are examined. Learners' attitudes towards these platforms are analyzed, considering socio-cultural, contextual, and individual factors. Challenges such as technical issues, data privacy, and ethical considerations are addressed. Despite challenges, AI-driven mobile learning shows promise in personalizing instruction, fostering adaptive learning pathways, and enhancing language acquisition experiences. Future research should focus on innovative pedagogical models, longitudinal studies, and interdisciplinary collaborations to maximize the potential of AI in ELT.